What Solvent is Actually the Best for Extracting Andrographolide? – Computational Evaluation of the Atomic Behavior in Different Solvent Models - Arif Setiawansyah; Khairunnisa Khairunnisa; Mayaranti Wilsya (Sinteza, 2026)
Andrographolide, a bioactive diterpenoid lactone from Andrographis paniculata, exhibits significant anti-inflammatory, antimicrobial, and anticancer properties, making solvent selection critical for optimizing extraction efficiency while preserving bioactivity. This study aimed to identify the optimal solvent for andrographolide extraction through computational evaluation of solvation thermodynamics and electronic properties using density functional theory. Geometry optimization and solvation calculations were performed at the B3LYP/def2-SVP level using the Conductor-like Polarizable Continuum Model (CPCM) in ORCA version 6.0.1 across twelve solvent systems including water, alcohols, aprotic solvents, and non-polar media. Molecular properties including solvation free energy, frontier molecular orbitals, global chemical reactivity descriptors, dipole moment, atomic charge distribution, molecular electrostatic potential, and infrared spectra were systematically analyzed. Results demonstrated that water exhibited the most favorable solvation free energy at -76.64 kJ/mol, superior to all other examined solvents including acetonitrile (-75.30 kJ/mol), methanol (-75.05 kJ/mol), and significantly better than hexane (-33.52 kJ/mol). Water induces optimal dipole moment enhancement to 1.253 Debye while maintaining stable HOMO-LUMO energy gap of 5.009 eV and consistent global reactivity descriptors, confirming preservation of intrinsic chemical properties and bioactivity. Infrared spectroscopic analysis revealed complete structural integrity in aqueous environment. This computational study establishes water as the superior extraction medium for andrographolide based on exceptional thermodynamic favorability, optimal electronic stabilization, maintained molecular stability, and practical advantages including non-toxicity and environmental sustainability.